Catalyst Development in the Dehydrogenative Borylation of Alkenes for the Synthesis Vinylboronate Esters - Li, Sida; Cui, Xin; Wang, Yue; Wu, Lipeng (Synlett, 2020)
Catalytic dehydrogenative borylation of alkenes provides an efficient and straightforward method for the preparation of synthetically useful vinylboronate esters. Here, we present a summary of developments and recent advances in this area, classified according to the various reactants and catalyst systems.1 Introduction2 Catalytic Dehydrogenative Borylation of Alkenes by Using Boranes3 Catalytic Dehydrogenative Borylation of Alkenes by Using Diboranes4 Zirconium-Catalyzed H2–Acceptorless Dehydrogenative Borylation of Alkenes with Boranes5 Conclusion and Outlook
Keywords: catalysis; borylation; dehydrogenation; vinylboronate esters; alkenes